1996
DOI: 10.2190/h6ju-05g8-xrpw-8ep5
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Analyses on the Effects of Type of Instructional Control on Learning from Computer-Based Instruction

Abstract: The purpose of this study was to analyze motivational effects of type of instructional control on learning from computer-based instruction, according to Keller's ARCS model of motivational design. Forty-eight sixth graders were randomly assigned to either learner or program control groups. Instructional materials were computer-based instructional programs for teaching four concepts utilized in advertisement propaganda techniques. The post-test with fifteen items for learning and Instructional Motivation Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…As predicted, results of this second experiment indicate an increase in affective engagement despite no increase or even a decrement in cognitive processing. In addition, the results of Experiment 2 are consistent with previous reports of a decrease in learning in student-paced versus teacher-controlled learning environments (Hannafin & Sullivan, 1996;Yang & Chin, 1997).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As predicted, results of this second experiment indicate an increase in affective engagement despite no increase or even a decrement in cognitive processing. In addition, the results of Experiment 2 are consistent with previous reports of a decrease in learning in student-paced versus teacher-controlled learning environments (Hannafin & Sullivan, 1996;Yang & Chin, 1997).…”
Section: Discussionsupporting
confidence: 88%
“…Hannafin and Sullivan (1996) found that college students assigned to a self-controlled instructional condition performed more poorly on cognitive tasks than on other-controlled instruction. Yang and Chin (1997) reported similar results with sixth-grade students. In both of those studies, students in the self-controlled condition were more satisfied with their learning and performance than were those in the program-controlled condition.…”
Section: Autonomy and Choice In Learningsupporting
confidence: 70%
“…A study by Eom and Reiser (2000) reported that sixth-and seventh-grade students who were allowed to control their instruction performed significantly worse than those who did not have control. Several researchers (Farrell andMoore 2000-2001;Morrison et al 1992;Swaak and de Jong 2001;Yang and Chin 1996) have reported that giving learners control over their instruction results in little or no improvement in achievement.…”
mentioning
confidence: 99%
“…Specifically, participants who were given choice options showed more favorable attitudes regarding their participation, greater perceived control over the experiment, and more interest in the story (Schraw et al, 1998; see also Flowerday & Schraw, 2003). In a similar vein, studies indicate that learners with choice options (e.g., self-controlled learning environments) are more satisfied with their learning and performance than learners without choice options (Hannafin & Sullivan, 1996;Yang & Chin, 1997). One of the most influential theories for individuals' postchoice states is cognitive dissonance (Festinger, 1957).…”
Section: After Choice: Cognitive Dissonancementioning
confidence: 92%